Pharmacodynamic Evaluation of Shenfu Injection in Rats With Ischemic Heart Failure and Its Effect on Small Molecules Using Matrix-Assisted Laser Desorption/Ionization–Mass Spectrometry Imaging - Wu, Hao; Dai, Zhenfeng; Liu, Xi; Lin, Ming; Gao, Zeyu; Tian, Fang; Zhao, Xin; Sun, Yi; Pu, Xiaoping (Frontiers in Pharmacology, 2019)
Objectives: We aimed to evaluate the effect of Shenfu injection in a rat model of ischemic heart failure and explore its mechanism. Methods: A rat model of ischemic heart failure after myocardial infarction was established by ligating the left anterior descending coronary artery. Forty-eight hours after surgery, the rats were intraperitoneally administered Shenfu injection for 7 weeks. Then, left ventricular fractional shortening and left ventricular ejection fraction were measured using transthoracic echocardiography, whereas heart rate and left ventricular end-diastolic pressure were measured using a MD3000 biosignal acquisition and processing system. The hearts and lungs of the rats were excised and weighed to measure the heart and lung weight indexes. In addition, cardiac histopathological changes were observed via hematoxylin–eosin and Masson’s trichrome staining, and serum cardiac troponin content was detected using a cardiac troponin ELISA kit. Furthermore, matrix-assisted laser desorption/ionization–mass spectrometry imaging was used to detect the levels and distribution of small molecules in the hearts of rats with ischemic heart failure. Results: We found that Shenfu injection can significantly increase left ventricular fractional shortening and left ventricular ejection fraction in rats with ischemic heart failure and significantly reduce the left ventricular end-diastolic pressure, heart and lung weight indexes, and cardiac troponin content; improve cardiac tissue morphology; and reduce infarct size. In addition, the matrix-assisted laser desorption/ionization–mass spectrometry imaging results demonstrated that 22:6 phospholipids were predominately distributed in the non-infarct zone, whereas 20:4 phospholipids tended to concentrate in the infarct zone. Shenfu injection significantly reduced taurine, glutathione, and phospholipids levels in the hearts of rats with ischemic heart failure and primarily changed the distribution of these molecules in the non-infarct zone. Conclusion: Shenfu injection induced obvious myocardial protective effects in rats with ischemic heart failure by stimulating antioxidation and changing the phospholipid levels and distribution.